Global longitudinal strain corrected by RR interval is a superior predictor of all‐cause mortality in patients with systolic heart failure and atrial fibrillation. (11th October 2017) - Modin, Daniel; Sengeløv, Morten; Jørgensen, Peter Godsk; Bruun, Niels Eske; Olsen, Flemming Javier; Dons, Maria; Fritz Hansen, Thomas; Jensen, Jan Skov; Biering‐Sørensen, Tor
Abstract: Aims: Quantification of systolic function in patients with atrial fibrillation (AF) is challenging. A novel approach, based on RR interval correction, to counteract the varying heart cycle lengths in AF has recently been proposed. Whether this method is superior in patients with systolic heart failure (HFrEF) with AF remains unknown. This study investigates the prognostic value of RR interval‐corrected peak global longitudinal strain GLSc = GLS/[RR^(1/2)] in relation to all‐cause mortality in HFrEF patients displaying AF during echocardiographic examination. Methods and results: Echocardiograms from 151 patients with HFrEF and AF during examination were analysed offline. Peak global longitudinal strain (GLS) was averaged from 18 myocardial segments obtained from three apical views. GLS was indexed with the square root of the RR interval GLSc = GLS/[RR^(1/2)]. Endpoint was all‐cause mortality. During a median follow‐up of 2.7 years, 40 patients (26.5%) died. Neither uncorrected GLS ( P = 0.056) nor left ventricular ejection fraction ( P = 0.053) was significantly associated with all‐cause mortality. After RR^(1/2) indexation, GLSc became a significant predictor of all‐cause mortality (hazard ratio 1.16, 95% confidence interval 1.02–1.22, P = 0.014, per %/s^(1/2) decrease). GLSc remained an independent predictor of mortality after multivariable adjustment (age, sex, mean heart rate, mean arterial blood pressure, left atrial volume index, and E/e′) (hazard ratio 1.17, 95% confidence interval 1.05–1.31, P = 0.005 per %/s^(1/2) decrease). Conclusions: Decreasing GLSc = GLS/[RR^(1/2)], but not uncorrected GLS nor left ventricular ejection fraction, was significantly associated with increased risk of all‐cause mortality in HFrEF patients with AF and remained an independent predictor after multivariable adjustment.